Epistatic interaction between variations in the angiotensin I converting enzyme and angiotensin II type 1 receptor genes in relation to extent of coronary atherosclerosis. Issue 10 (15th September 2003) - Ye, S; Dhillon, S; Seear, R; Dunleavey, L; Day, L B; Bannister, W; Day, I N M; Simpson, I
Abstract : Objective: To test the hypothesis that gene–gene interaction of the renin–angiotensin system is associated with an effect on the extent of coronary atherosclerosis. Setting and results: A cohort of 1162 patients with coronary artery disease were genotyped for genetic polymorphisms in the renin–angiotensin system. Patients carrying the D allele of the angiotensin I converting enzyme (ACE) gene had greater coronary extent scores (defined as the number of coronary segments with 5% to 75% stenosis) than those not carrying this allele (p = 0.006 in non-parametric analysis and p = 0.019 in parametric analysis). This association remained significant after adjusting for age, body mass index, hypertension, and diabetes, which were also significantly associated with coronary extent scores. There was a significant interaction (p = 0.033) between genotypes of ACE and angiotensin II type 1 receptor (AGTR1). The association between the ACE gene D allele and increased coronary extent scores was significant (p = 0.008 in non-parametric and p = 0.027 in parametric analysis) in those carrying the +1166 C allele of the AGTR1 gene, but was absent in those not carrying the AGTR1 gene +1166 C allele. Conclusion: These findings suggest that variation in the ACE and AGTR1 genes and their interaction may not only contribute to susceptibility of coronary artery disease as previously found but also modify the disease process, thus contributing to interindividual differences in severity of the disease.